The Effect Of Planting Distance and Dosage Of Fertilizing Cow Manage On Production Products Red Rosella (Hibiscus sabdariffa L.) - Mohamad Iswanto; M Abror (Procedia of Engineering and Life Science, 2022)
This study aims to determine the effect of spacing and application of manure on the production of Red Roselle (Hibiscus sabdariffa L.). The research was carried out in three months, from April to June 2021. This research was carried out using a factorial Randomized Group Design (RAK). Namely, the first factor is the spacing between (i) 20 x 10 cm (J1); (ii) 20 x 20 cm (J2); 20 x 30 cm (J3). The second factor includes (i) 0 ton/hectare (D1); (ii) 5 tons/ha (D2); (iii) 10 tons/ha (D3). Produced 9 treatment combinations and each was repeated 3 times resulting in 27 experimental units. The variables in this study were plant length, number of leaves, flower wet weight and flower dry weight. The data in this study used analysis of variance (ANOVA) if there was a significant difference, then the Honest Significant Difference (BNJ) test was continued at the 5% confidence level. The results showed that there was a significant interaction on the observed variables of plant growth, namely plant height at 41 DAP. In the observation variable the number of leaves there was a significant interaction at the age of 34 DAP and a very significant effect on the spacing treatment at 41 DAP and 48 DAP. However, the observation of plant production showed no significant response to the wet weight of flowers and dry weight of flowers.